Effective teaching of manual skills to physiotherapy students: a randomised clinical trial. Issue 8 (August 2017) - Rossettini, Giacomo; Rondoni, Angie; Palese, Alvisa; Cecchetto, Simone; Vicentini, Marco; Bettale, Fernanda; Furri, Laura; Testa, Marco
Abstract : Context: To date, despite the relevance of manual skills laboratories in physiotherapy education, evidence on the effectiveness of different teaching methods is limited. Objectives: Peyton's four‐step and the 'See one, do one' approaches were compared for their effectiveness in teaching manual skills. Methods: A cluster randomised controlled trial was performed among final‐year, right‐handed physiotherapy students, without prior experience in manual therapy or skills laboratories. The manual technique of C1–C2 passive right rotation was taught by different experienced physiotherapist using Peyton's four‐step approach (intervention group) and the 'See one, do one' approach (control group). Participants, teachers and assessors were blinded to the aims of the study. Primary outcomes were quality of performance at the end of the skills laboratories, and after 1 week and 1 month. Secondary outcomes were time required to teach, time required to perform the procedure and student satisfaction. Results: A total of 39 students were included in the study (21 in the intervention group and 18 in the control group). Their main characteristics were homogeneous at baseline. The intervention group showed better quality of performance in the short, medium and long terms ( F 1, 111  = 35.91, p < 0.001). Both groups demonstrated decreased quality of performance over time ( F 2, 111  = 12.91, p < 0.001). The intervention group reported significantly greater mean ± standard deviation satisfaction (4.31 ± 1.23) than the control group (4.03 ± 1.31) (p < 0.001). Although there was no significant difference between the two methods in the time required for teaching, the time required by the intervention group to perform the procedure was significantly lower immediately after the skills laboratories and over time (p < 0.001). Conclusions: Peyton's four‐step approach is more effective than the 'See one, do one' approach in skills laboratories aimed at developing physiotherapy student competence in C1–C2 passive mobilisation.